The Cunning of Song. Homer the Rhapsodist or the Parody of War - Mejía Toro, Jorge Mario (Estudios de Filosofía, 2006)
Starting from some contemporary philological studies on the meaning of the name rhapsodist, that busy themselves with the more ancient interpretations of the term and come to associate it with the ruse, the trick, cunning, we try to derivóte the conception of the Poetry that Homer materializes in the Iliad, which implies then to decide if the rhapsodist is the oaede composer or only the reciter of the finished work. And the sense of his act as a knitting chants together or singing with a truncheon depends, in turn, on the fact of the oral transmission of the poem being equivalent or not to the inexistence of the written composition, and if this is a simple copying down and a conservation or, rather, an essential score of Poetry.